EFEKTIFITAS PERMAINAN SIMULASI UNTUK MENINGKATKAN HUBUNGAN INTERPERSONAL PESERTA DIDIK SEKOLAH DASAR - Fatmah, Hawinda Widya; Lilik, Salmah; Abdat, Chadidjah Husain (Universitas Sebelas Maret, 2014)
The aims of the research was to determine the effectiveness of game simulation used snakes and ladders media to fostering elementary students? interpersonal relationships. This was Guidance and Counseling Action Research with the subject of research were five students of fifth grade, who have difficulty for interlacing interpersonal relationships. Preliminary studies and collecting data use interviews and observation instruments. The study was conducted in three cycles of action. The data result of research were obtained from the observation during game activities happen use observation sheet and interview. Researchers gives a pretest and posttest using the observation sheet and students are given guidance group technique of game simulation media snakes and ladders. The validity of the data was gained through data, method and theory triangulation technic. The analysis of data use the percentage analysis and then committed clinical analysis. The results of research showed that group guidance group technique of game simulation media snakes and ladders is able to improve interpersonal relationships of fifth grade students in Elementary School. The statement is evidenced by an increase in the average yield percentage of students interpersonal relationships for each cycle , the first cycle is 32.3% , the second cycle is 45.55% and the third cycle is 86,17%.